Field-induced pseudo-skyrmion phase in the antiferromagnetic kagome lattice - Villalba, Martin Emilio (2019)
We study the effects of an in-plane Dzyaloshinskii-Moriya interaction under an external magnetic field in the highly frustrated kagome antiferromagnet. We focus on the low-temperature phase diagram, which we obtain through extensive Monte Carlo simulations. We show that, given the geometric frustration of the lattice, highly nontrivial phases emerge. At low fields, lowering the temperature from a cooperative paramagnet phase, the kagome elementary plaquettes form noncoplanar arrangements with nonzero chirality, retaining a partial degeneracy. As the field increases, there is a transition from this “locally chiral phase” to an interpenetrated spiral phase with broken Z3 symmetry. Furthermore, we identify a quasi-skyrmion phase in a large portion of the magnetic phase diagram, which we characterize with a topological order parameter, the scalar chirality by triangular sublattice. This pseudo-skyrmion phase consists of a crystal arrangement of three interpenetrated non-Bravais lattices of skyrmionlike textures, but with a non-(fully)-polarized core. The edges of these pseudo-skyrmions remain polarized with the field, as the cores are progressively canted. Results show that this pseudo-skyrmion phase is stable up to the lowest simulated temperatures and for a broad range of magnetic fields.